Choosing the Right Trees: Setting Priorities for Multipurpose Tree Improvement - Franzel, Steven; Jaenicke, Hannah; Janssen, Willem G. (International Service for National Agricultural Research, 1996)
Setting priorities among tree species for genetic improvement research, involves an integration of researchers' and farmers' perspectives for choosing those species that will give the greatest benefits. The process requires both socioeconomic and biophysical expertise and begins with an assessment of users', that is resource-poor farmers', needs. Researchers conduct region-wide surveys to determine farmers' preferences among species and, at meetings, assess candidate species according to their researchability, expected adoption, and policy objectives. Once a short list of a few (e.g. 4 to 6) species is drawn up from the above exercises, researchers conduct field surveys to estimate the value of the tree products from these species and validate and rank the species. This prioritization procedure is flexible; it can be adapted to meet the specific needs of the researchers. To set priorities for research is no new task. However, the procedures presented in this document are innovative; they are structured and objective, and involve both researchers and farmers. The procedures have been tested in the humid lowlands of West Africa (HULWA) and are being further refined in other areas.